Track Surface Identification Using an Instrumented Horseshoes. (June 2014) - Martin, C; Merritt, J; Davies, H
Abstract : Introduction: Track conditions in Thoroughbred racing significantly impact performance and injury. However, surface effects on limb biomechanics at racing speeds are poorly understood. Methods: A racing shoe was modified to contain inertial transducers and a strain gauge to provide motion kinematics and a measure of hoof/surface interaction load. A two‐phase non‐linear surface reaction model was defined to represent the hoof deceleration phase, and the hoof penetration phase where the surface reaction force was represented by a quartic stiffness profile and a fixed damping term. Model parameters were determined using an "output error" iteration method for 25 strides at medium gallop. Parameters were compared using a standard t‐test. Results: The sand track had a significantly greater (P<0.0001) maximum penetration of 61 ± 10 mm (mean ± SD), than the grass track (41 ± 0.5 mm). Both stiffness parameters were significantly different between the two tracks (P<0.0001), but damping parameters did not differ significantly. Hoof impact at high speed involved decelerations of over 100 'g' occurring within milliseconds. Conclusions: This study demonstrated that a surface reaction model using data acquired from an instrumented horseshoe, distinguished between surface reaction profiles of a sand track and a grass track, as a step towards improving track rating methods. A further challenge will be to develop independent checks on instrument calibrations. Ethical Animal Research: The study was approved by the University of Melbourne Animal Ethics Committee.Sources of funding: This study was funded by the Rural Industries Research and Development Corporation under project PRJ‐006479, and by a University of Melbourne Research Collaboration Grant.Competing interests: Colin Martin is the Director of SPERERO Pty. Ltd. a consulting and innovations company.